Comparison of the efficacy and tolerability of simvastatin and atorvastatin in the treatment of hypercholesterolemia - Recto, Cesar S. (Clin Cardiol, 2009)
Background: Simvastatin and atorvastatin are effective statins for treating hypercholesterolemia. Hypothesis: The study was undertaken to compare the efficacy and tolerability of simvastatin 20 and 40 mg/day and atorvastatin 10 and 20 mg/day. Methods: In this multinational, open‐label, crossover study, 258 patients with primary hypercholesterolemia were randomized after 4 weeks of diet plus placebo to once‐daily administration of a starting dose sequence of simvastatin (20 mg) or atorvastatin (10 mg), or a higher dose sequence of simvastatin (40 mg) or atorvastatin (20 mg) for 6 weeks. Patients were then switched after a 1‐week washout to the corresponding starting or higher dose of the alternate drug for a second 6‐week period. The primary endpoint was the mean percent change from baseline to Week 6 in low‐density lipoprotein (LDL) cholesterol; percent changes from baseline in total cholesterol, high‐density lipoprotein cholesterol, triglycerides, and apolipoprotein B were also compared. Safety was assessed through adverse experiences and laboratory measurements. Results: Both statins produced statistically significant improvements in all measured plasma lipids and lipoproteins. The main treatment comparison showed no statistically significant difference in changes in LDL cholesterol and triglycerides, whereby the overall effects were comparable when doses of 20 mg and 40 mg of simvastatin were compared with atorvastatin 10 mg and 20 mg. The mean percent reductions for LDL cholesterol from baseline to Week 6 ranged from 35–42% for the entire study cohort. An LDL cholesterol level ≤ 130 mg/dl (3.4 mmol/l) was achieved in approximately 70% of patients treated with both drugs in this study. Simvastatin and atorvastatin were well tolerated at the doses studied. Conclusion: In patients with hypercholesterolemia, the most commonly used doses of simvastatin and atorvastatin produced similar changes in LDL cholesterol and achieved an LDL cholesterol level ≤ 130 mg/dl (3.4 mmol/l) in a similar number of patients. Both statins were well tolerated.